"No Seat at the Party": Mobilizing White Masculinity in the Men's Rights Movement. Issue 1 (2nd January 2022) - Carian, Emily
ABSTRACT: I use the men's rights movement, an anti-feminist backlash movement consisting largely of straight, white men, to examine how high-status group members develop a collective identity leveraged by right-wing movements. Drawing on 31 interviews with men's rights activists, I find that masculinity, whiteness, and straightness play crucial roles in motivating identification with the movement. Interviewees believe others see them as privileged and thus immoral because of these identities. This clashes with the way they see themselves, threatens their moral sense of self, and evokes negative emotions. In response, they reconstruct themselves – as straight, white men – as victims, thus developing a sense of "we" and a basis for collective action. In an effort to recoup a sense of moral goodness and build community, they also construct a new collective identity as men's rights activists, which invests them in organized backlash. This paper develops a theory to explain collective identity formation among high-status group members, and illustrates how the identity work straight, white men undertake in the face of culturally legitimate challenges to their privilege can invest them in organized backlash movements.